Study of mixed integer programming models for the concrete delivery problem - Hernández López, Óscar Alejandro (2020)
Objectives and Methods of Study: The main objective of this research is the study of Mixed Integer Programming (MIP) formulations for the Concrete Delivery Problem (CDP).